Beginning Java with WebSphere - Janson, Robert W. (Apress Imprint: Apress, 2013)
Beginning Java with WebSphere provides a step-by-step guide for creating and installing both client- and server-based Java applications using Rapid Application Development v8, WebSphere Application Server 8.0, and Java. Since more and more Java applications are moving to the server and using HTML for the user interface, there is a minimal amount of time spent exploring the Java GUI components. More specifically, this book covers graphical user interfaces using RAD's Visual Editor, variables, conditional logic, and application improvements/enhancements from the client side. And, from the server-side, this book covers servlets, JavaServer Pages (JSPs), database accessibility (JDBC), custom tags, and concludes with JavaServer Faces (JSFs). This book concentrate on base topics that allow you to get to the server-side and database topics quickly.